2003
DOI: 10.3171/jns.2003.98.5.0967
|View full text |Cite
|
Sign up to set email alerts
|

Transsphenoidal microsurgical treatment of Cushing disease: postoperative assessment of surgical efficacy by application of an overnight low-dose dexamethasone suppression test

Abstract: Transsphenoidal microsurgery is an effective means of control for patients with adrenocorticotrophic hormone-producing microadenomas. Clinical outcome correlated well with the size of the tumor, as measured on preoperative imaging studies, and with postoperative morning cortisol levels following an overnight dexamethasone suppression test. Postoperative cortisol levels can be used as a useful prognostic indicator of the likelihood of future recurrence following transsphenoidal adenomectomy in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
2
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 39 publications
5
118
2
8
Order By: Relevance
“…Similarly, Fahlbusch et al reported that levels less than 2 µg/dl are good predictors of cure (53). Other studies suggest that values of < 3 µg/dl (26), < 5 µg/dl (69), < 100 nmol/l (25), or < 8 µg/dl (70) could better identify those patients on CD remission.…”
Section: Low-dose Dexamethasone Cortisol Suppressionmentioning
confidence: 99%
“…Similarly, Fahlbusch et al reported that levels less than 2 µg/dl are good predictors of cure (53). Other studies suggest that values of < 3 µg/dl (26), < 5 µg/dl (69), < 100 nmol/l (25), or < 8 µg/dl (70) could better identify those patients on CD remission.…”
Section: Low-dose Dexamethasone Cortisol Suppressionmentioning
confidence: 99%
“…Six studies reported both early and late remission rates (6,27,34,40,42,44,47), with an early remission rate of 75.6% (476/639 patients; range 66.7-89.0%) compared with a late remission rate of 72.3% (342/473 patients; range 50.0-96.9%; PZnot significant (NS)). The effect of tumor size on remission outcomes of initial microscopic TSS was available from 18 and 16 studies for microadenomas and macroadenomas respectively.…”
Section: Remission Ratesmentioning
confidence: 99%
“…Transsphenoidal surgery (TSS) remains the procedure of choice with immediate post-operative remission rates ranging between 59 and 94% in major centres (6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21). The reason for this wide range is the variability in defining remission in each study, the inclusion or not of macroadenomas, and the number of the patients studied, rendering the interpretation of results problematic.…”
Section: Introductionmentioning
confidence: 99%